Saisonnalité de ponte de Crassostrea gigas et Crassostrea angulata dans le bassin de Marennes-Oléron. Un demi siècle de résultats : 1950-2000. La différence dans la saison de ponte reflète-t-elle une différence entre taxons ou l'évolution climatique ? - Soletchnik, Patrick (2001)
The Marennes-Oléron Bay on the Atlantic coast is a major oyster culture centre in France. 40 000 tonnes of cupped oysters are produced there each year. The two taxa C. angulata and C. gigas have been cultured in turn over the last century. Since 1950, larvae have been captured between June and September in the southern part of the Bay, near the mouth of the Seudre River, the traditional oyster spat capture zone. This historical database shows that the frequency of larvae capture is defined by three to four peaks in larvae emission in C. angulata and only two peaks for C. gigas during a single season. Seventeen years of data on C. angulata between 1950 and 1969 and 27 years for C. gigas between 1972 and 2000 demonstrate that the beginning of the spawning season occurs, on average, in mid-June for C. angulata and late June for C. gigas. Fifty percent of spawning events have occurred by mid-July for C. angulata and by the last two weeks in July for C. gigas. While the difference in spawning intensity can be phenotypic, the 15 day shift in the season between the two taxa does not correspond to the patterns of maturation demonstrated in the two taxa. In light of climate change of the end of the 20th century, this study shows that the 15 day "advance" in the mean spawning season is not likely to be due to the change in taxon. A study conducted in 2000 on both taxa showed that C. angulata spawned later compared to C. gigas. The increase in temperature of more than 1°C in 25 years, the 10-15% decrease in mean insolation (average daily irradiance) in the Bay as well as the significant increase in spring rainfall all act on the food chain of the estuarine ecosystem and on the seasonal variability in abundance of food sources available for oysters. The delay in the onset of phytoplankton blooms may induce the delay in spawning that has been observed for the last three decades. Le bassin de Marennes-Oléron sur la cote atlantique est un haut lieu de l'ostréiculture française. 40 000 tonnes d'huîtres creuses y sont ...